COMPARSION BETWEEN CBR PROTOCOL AND LEACH PROTOCOL USING NS2 AND TDMA - Manimekala, Ms.B. (IJRDO -Journal of Computer Science Engineering, 2016)
Technological advances incommunications and computation have enabledthe development of low-cost, low-power, small insize, and multifunctional sensor nodes in awireless sensor network. Since the radiotransmission and reception consumes a lot ofenergy, one of the important issues in wirelesssensor network (WSN) is the inherent limitedbattery power within network sensor nodes. Inaddition to maximizing the lifespan of sensornodes, it is preferable to distribute the energydissipated throughout the wireless sensornetwork in order to maximize overall networkperformance. Packet loss that occurs due tomobility of the sensor nodes is one of mainchallenge in Wireless Sensor Network (WSN)and it comes in parallel with energyconsumption. CBRP can change TDMAscheduling adaptively according to traffic andmobility characteristics. In this protocol thecluster head receive data from not only itsmember during the TDMA allocated time slotbut also other sensor nodes that just enter thecluster when it has free timeslots, each clusterhead takes turn to be the free cluster head in thenetwork. The performance of proposed CBRprotocol is evaluated using NS-2 and comparedwith LEACH protocol